Differentiation strategies and winery financial performance: An empirical investigation - Sandra K. Newton; Armand Gilinsky; Douglas Jordan (Wine Economics and Policy, 2015)
This investigation into small-to-medium sized wine businesses empirically tests linkages among differentiation strategies and financial performance over time. Using a two-by-two model, we examine the impact of differentiation strategies on profitability and growth. Financial and operational data from a proprietary database of 71 United States wineries, encompassing five continuous years (2006-2010), provide longitudinal robustness. Management decisions regarding resources and capabilities are used to cluster the sample firms into a two-by-two differentiation strategy model. Those wineries sourcing over 50% estate grapes and distributing over 50% direct-to-consumer have higher gross margins compared to other clusters. Direct-to-consumer distribution decisions impact growth. Results of this research indicate that distribution channel choice-direct-to-consumer-positively impacts gross profit margin and winery growth rates. Supply chain choice-sourcing estate grapes also positively impacts gross profit margin. This study uses reported financial data that have not been made available to researchers.
Keywords: 330; Competitive strategy; Differentiation; Financial performance; Small and medium-sized enterprises (SME); Wine industry